Antigenic variation in strains of avian infectious bronchitis virus - Dawson, P. S. (Arch Gesamte Virusforsch, 1971)
Fifteen british field strains of IBV were compared using cross serum neutralization tests in embryonated eggs with seven standard reference strains of IBV. While the British field strains were considered to form a relatively homogeneous group considerable antigenic variation did occur. It was considered that it was not feasible at this time to describe accurately a serotype classification for IBV, similar to that described for other virus groups.